Graphene oxide coated side polished surface plasmon resonance optical fibre sensor with varying polishing losses - Shanmuga Vadivu, N.; Zakaria, Rozalina; Mezher, Mezher H.; Maheswar, R.; Lim, C.S.; Lai, D.; Amiri, Iraj Sadegh (Springer, 2019)
Four batches of side-polished SMF optical fibres with different polishing losses, − 0.5 dBm, − 5 dBm, − 10 dBm and − 15 dBm were coated with a graphene oxide layer of ~ 0.5 μm via drop casting. TE polarized light was propagated through the light during experiments and four different transformer oils with different water contents were dropped onto the sensor. The drop in the power of transmitted light was recorded. The responses of the sensors showed good linearity for all, but the least polished fibre showed the weakest response in terms of power drop towards change in concentration. The − 5 dBm fibre showed the best response per unit concentration change. Additional tests showed the increased response for a GO coated side polished sensor compared to an uncoated side polished sensor. Simulation using COMSOL was performed to show the effects on the electric field of a sensor with and without GO coating. Another set of simulations were performed to show the effects of reducing cladding thickness on the coupling of the electric field. Simulations show that the optimal cladding thickness is not the most polished fibre, coinciding with our results that − 15 dBm loss fibre did not show the most response per unit change in the analyte. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.